2014
DOI: 10.1080/15381501.2013.775686
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Step Process for Interactive Parent–Adolescent Communication About HIV Prevention: Advice From Parents Living With HIV/AIDS

Abstract: AIM This study investigated how parents living with HIV communicated about HIV prevention with their 10–18 year old children. METHODS Interviews with 76 mothers and fathers were analyzed for (1) their experiences discussing HIV prevention with adolescents, and (2) advice on how to best broach HIV-related topics. RESULTS Interactive conversations, where both parents and adolescents participated, were regarded as effective. Parents emphasized that adolescents should have a “voice” (be able to voice their con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Daughters agreed that mothers’ candidness contributed to communication about sexual risks (Cederbaum, 2012; Cox, Mezulis, & Hyde, 2010). Interactive communication strategies include making sure adolescents’ voices are heard to encourage active exchange of questions and answers, assessing current knowledge and leaving room for future discussions (Edwards & Reis, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Daughters agreed that mothers’ candidness contributed to communication about sexual risks (Cederbaum, 2012; Cox, Mezulis, & Hyde, 2010). Interactive communication strategies include making sure adolescents’ voices are heard to encourage active exchange of questions and answers, assessing current knowledge and leaving room for future discussions (Edwards & Reis, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated that a majority of mothers living with HIV/AIDS are comfortable in discussing their status and providing advice on HIV/AIDS risk to their children (Edwards, Reis, & Weber, 2013; O’Sullivan et al, 2005). Having a parent that lives with HIV/AIDS has been shown in studies to motivate and facilitate the discussion of safe sex practices in their HIV negative children (Cederbaum, 2012; Edwards, Reis, & Weber, 2013; Edwards & Reis, 2014; O’Sullivan et al, 2005). Children of parents living with HIV/AIDS that maintain open communication regarding HIV risk have been shown to be engage in limited sexually risky behaviors leading into adulthood (Murphy, Roberts, & Herbeck, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Normative Model of Interpersonal Communication (NMIC) (Goldsmith, 2001) focuses on describing, categorizing and explaining communication that has already occurred, including situational and contextual factors. Specific to parent-child communication, the NMIC is useful because it encourages researchers to provide a thoughtful analysis of conversations that have already taken place (e.g., contexts of HIV prevention conversations) (Edwards & Reis, 2014). NMIC was used to explain the strategies that parents used to discuss HIV prevention with their daughters.…”
Section: Introductionmentioning
confidence: 99%
“…The communication in most cases are unidirectional and takes the form of a lecture rather than dialogue and the consequences of sex were exaggerated, and what triggered the conversation was often the undesirable behaviour of the adolescents [11,12]. In addition, directive parents who tend to have a more authoritarian communication style do not invite open discussion and questions from children, few fathers provided explicit guidance, open and honest conversations which contributed to 5 making sure adolescents' voices are heard to encourage an active exchange of questions and answers, assessing current knowledge and leaving room for future discussions [14].…”
Section: Introductionmentioning
confidence: 99%